2005
DOI: 10.1093/jpepsy/jsj013
|View full text |Cite
|
Sign up to set email alerts
|

Identifying, Recruiting, and Enrolling Adolescent Survivors of Childhood Cancer into a Randomized Controlled Trial of Health Promotion: Preliminary Experiences in the Survivor Health and Resilience Education (SHARE) Program

Abstract: Health promotion RCTs among adolescent survivors of childhood cancer may help prevent and control the onset and severity cancer-treatment-related late effects. However, trial success may be contingent upon tracing nonresponsive adolescents and reducing and eliminating barriers to participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…29 Research examining knowledge about clinical trials among children and adolescents has delineated a lack of understanding of what clinical trials are, the difference between clinical versus nonclinical research treatments, and incorrect assumptions about the level of invasiveness of clinical trial interventions compared with standard treatments. 30,31 Misinformation and a lack of awareness may also be the result of poor readability, understandability, and clarity of consent forms used in child and adolescent cancer research and clinical trials. 32,33 A medical provider' s knowledge of available clinical trials and communication about clinical trial information can also affect an adolescent' s awareness level.…”
Section: Information Knowledge and Awareness About Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Research examining knowledge about clinical trials among children and adolescents has delineated a lack of understanding of what clinical trials are, the difference between clinical versus nonclinical research treatments, and incorrect assumptions about the level of invasiveness of clinical trial interventions compared with standard treatments. 30,31 Misinformation and a lack of awareness may also be the result of poor readability, understandability, and clarity of consent forms used in child and adolescent cancer research and clinical trials. 32,33 A medical provider' s knowledge of available clinical trials and communication about clinical trial information can also affect an adolescent' s awareness level.…”
Section: Information Knowledge and Awareness About Clinical Trialsmentioning
confidence: 99%
“…22 One study examining adolescent cancer survivor enrollment in randomized controlled trials reported that a lack of time and proximity to the treatment site were primary reasons for refusal of participation. 31 …”
Section: Sociodemographic Factorsmentioning
confidence: 99%
“…Hinds et al (2006) pointed out that AYAs with cancer, similar to most individuals in this age group, are active users of Web-based technology and the use of chat rooms and other discussion forums to describe their experiences with cancer. Researchers involved with childhood cancer survivors recognized the need to use technology for meeting the long-term needs of childhood cancer survivors (Dalton, 2005; Tercyak et al, 2006). Internet-based clinical trials are now considered feasible (McAlindon, Formica, Kabbara, LaValley, & Lehmer, 2003).…”
Section: Study Protocolmentioning
confidence: 99%
“…Survivors of pediatric cancer are a challenging clinical population to recruit and retain as research participants (Hinds, Burghen, Haase, & Phillips, 2006; Patenaude & Kupst, 2005; Smith & Hare, 2004; Tercyak, Donze, Prahlad, Mosher, & Shad, 2006). The recruitment and retention of older adolescent and young adult (AYA) childhood cancer survivors for research studies may be even more challenging because of their developmental stage, lifestyle characteristics, and less frequent contact with pediatric oncology centers (Tercyak et al, 2006).…”
mentioning
confidence: 99%
“…Most research on resilience has focused on particular groups who have experienced particular trauma, for example during childhood (Castro, Garfinkle, Naranjo, Rollins, Brook, & Brook, 2007;Ireland, Weisbart, Dubowitz, Rowe, & Stein, 2010;Tercyak, Donze, Prahlad, Mosher, & Shad, 2006) and adolescence (Ali, Dwyer, Vanner, & Lopez, 2010;Brown, 2001;Velleman, Templeton, & Copello, 2005). However, while extremely important, this work has limited applicability for understanding resilience (and developing appropriate policy responses) across wider communities.…”
Section: The Concept Of Resiliencementioning
confidence: 99%